Perancangan Aksesoris Fashion Dengan Sistem Modular di UKM Lori - Salsabila, Nadiah; Rosandini, Morinta; Viniani, Prafitra (Institut Seni Indonesia Yogyakarta, 2023)
This research focuses on the application of a modular system for fashion accessories at UKM LORI (Laras Ornament Indonesia), which requires design development using batik inspiration in collections to create new design variations. The method used in this research is qualitative by collecting literature study data, field observations in LORI SMEs, interviews with LORI SMEs owners, and experimental development of Banyuwangi batik motifs and applied to fashion accessories using metal materials. The results of this study are necklace accessories products with the application of a modular system, using Banyuwangi batik inspiration in its design. The results of this product can be used as inspiration in developing various accessories designs in LORI SMEs to reach new target markets for these SMEs.ABSTRAKPenelitian ini berfokus pada penerapan sistem modular pada aksesoris fashion di UKM LORI (Laras Ornamen Indonesia) yang membutuhkan pengembangan desain menggunakan inspirasi batik pada koleksi untuk membuat variasi desain baru. Metode yang digunakan pada penelitian ini adalah kualitatif dengan pengumpulan data studi literatur, observasi lapangan di UKM LORI, wawancara dengan pemilik UKM LORI, dan eksperimentatif pengembangan motif batik Banyuwangi, dan diaplikasikan pada aksesoris fashion menggunakan material logam. Hasil dari penelitian ini berupa produk aksesoris kalung dengan penerapan sistem modular, menggunakan inspirasi batik Banyuwangi pada desainnya. Hasil dari produk ini dapat dijadikan inpirasi dalam pengembangan variasi desain aksesoris di UKM LORI untuk menjangkau target market baru pada UKM tersebut.